VALUE OF PEDAGOGICAL PROFESSION: ANALYSIS OF ADVANTAGES OF TEACHING AS VIEWED BY SCHOOL TEACHERS - Jermolajeva, Jelena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
The professional values of a teacher form the core of his/her professional identity. They are manifested, among other things, in teacher’s views on the value and advantages of the profession. The aim of this paper is to analyse and compare the views of school teachers of Riga and Smolensk on positive aspects of the profession, and reveal theirs structure. To this aim, a survey was implemented, which involved 144 teachers from Latvia and Russia. Four main categories of advantages are identified in the massive of teachers’ answers; those of self-development and communication with students are the most often mentioned.